Evaluation of Productivity Rate and The Quality of Several Genotypes of Jatropha curcas Linn. Seeds at First and Second Year in East Java and West Nusa Tenggara, Indonesia - ., Maftuchah; Zainudin, Agus; Sudarmo, Hadi (International Journal of Engineering and Technology, 2019)
The research is aimed to obtain information regarding productivity rate and the quality of JatrophaÂ curcas Linn. seeds within two years period in Pasuruan-East Java and Lombok-West Nusa Tenggara (NTB). The seeds used were the hybrid of JC5(SP8XSP16), JC6(SP8XSP38), JC7(SP33XHS49), JC8(SM35XSP38), and control IP3-A dan IP3-P. At the first harvest in East Java there were not any differences in the harvest duration; otherwise, there was one in West Nusa Tenggara. The highest weight of dry seeds was JC18 (52.8 g/plant) and did not significantly differ among other three hybrids. At the planting ofÂ NTB, the highest dry weight of JC5 (191.94 g/plant) did not differ significantly from JC7 and JC18. At the second harvest in East Java, the highest dry weight of JC7 (233.44 g/plant) did not differ significantly from three other hybrids and IP3P. At the experiment in NTB, the highest dry weight of JC5 (318.75 g/plant) did not differ from three other genotypes of hybrids. The JC5 treatment produced the highest number of fruit and fruit bunches whereas the highest oil rate was gained by JC18 (32.09% in East Java and 33.04% in NTB). The four examined genotypes showed higher production rate than the control. The planting in NTB indicated higher production rate than those in East Java.Â Â Â